Motor-Vehicle Crash History and Licensing Outcomes for Older Drivers Reported as Medically Impaired in Missouri - Meuser, Thomas M. (2008)
The identification and evaluation of medically impaired drivers is an important safety issue. Medical fitness to drive is applicable to all ages but is particularly salient for older adults. Voluntary procedures, whereby various professionals and family members may report medical fitness concerns to State driver license bureaus, are common in the United States. This paper examines traffic crashes of drivers reported during 2001–2005 under the State of Missouri’s voluntary reporting law (House Bill HB-1536) and the resulting licensing outcomes. Missouri’s law is non-specific as to age, but the mean age of reported drivers was 80. Reports were submitted by police officers (30%), license office staff (27%), physicians (20%), family members (16%), and others (7%). The most common medical condition was dementia/cognitive (45%). Crash history for reported drivers was higher than that of controls, dating back to 1993, reaching a peak in 2001 when the crash involvement of reported drivers was 9.3% vs. 2.2% for controls—a fourfold difference. The crash involvement of reported drivers decreased rapidly after, indicating the impact of HB-1536 reporting with subsequent license revocation and to a lesser degree, mortality. Of the 4,100 reported individuals, 144 (3.5%) retained a driver’s license after the process.